Dinamika Pemikiran Hukum Islam di Indonesia - Jaih Mubarok (Unisia, 2003)
There are spesific trends in modern development of Islamic law in Indonesia. Most of the moslems are getting committed to theirown legal reasoning (ijtihad), or at least to the fatwa or legal decision given by ulama (moslem jurists) in the Islamic organization to which they join, instead of four classical established schools. As Indonesian Moslem do not recognize the concept of 'ishmah or ma'shum, the chance for liberalization of ijtihad is extremely huge.